Tunable mechanical properties of thermoplastic foams produced by additive manufacturing - Abdullah Alduais; Sezer Özerinc (eXPRESS Polymer Letters)
Fused deposition modeling (FDM) is a versatile additive manufacturing technique for producing polymeric parts. Incorporating a foaming agent into the filament material enables the FDM-printing of thermoplastic foams, which opens up new possibilities for achieving desired mechanical property combinations. This study explored the process-property design space of FDM-printed polylactic acid (PLA) foams. Tensile and compression specimens were produced at a wide range of printing parameters using a commercial thermoplastic filament containing a foaming agent. Increasing the nozzle temperature and decreasing the filament feed rate increased the extent of foaming. Adjustment of the nozzle temperature, feed rate, and infill ratio controlled porosity over a density range of 0.24 to 1.17 g/cm3. Tuning of the mechanical properties over an order of magnitude was demonstrated, with elastic moduli ranging from 0.24 to 3.7 GPa and tensile strength ranging from 4.2 to 34.5 MPa. The mechanical behavior closely followed the Gibson-Ashby model predictions. Foaming filaments provide a new tool for tuning the mechanical response of FDM-printed parts to achieve unique combinations of mechanical properties that are not attainable through conventional methods.